SOME IMPACTS OF THE FOURTH INDUSTRIAL REVOLUTION FOR LEARNING ATTITUDE OF THE POLITICAL THEORY SUBJECTS OF THE CURRENT STUDENTS - Võ Hoàng, Đông (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2021)
The Fourth Industrial Revolution has been changing the face of socio-economic life in the general world and in Vietnam, particularly. As a force of the young intellectuals of the country, current Vietnamese students are a class of people who live in the circumstances and conditions of the fast development of science and technology so that they are so sensitive to life and social change. Within the scope of this article, the author presents an overview of the positive effects and challenges of the fourth industrial revolution on the learning of political theory subjects of students at the current universities, colleges.